Digitalização dos serviços públicos, ambidestria e governança pública: evidências no Hospital Universitário Federal do Piauí - Sousa, Raquel Karoline Carvalho de (2022)
The objective of this study is to analyze how the interactions between digitalization of services, ambidexterity and public governance occur at the University Hospital of the Federal University of Piauí (HU-UFPI). The research strategy used was a case study, the subjects are employees of the University Hospital of the Federal University of Piauí - HU-PI, allocated in the Superintendence and in the three managements that manage the hospital: Teaching and Research Management, Administrative Management and Health Care Management, at strategic, tactical and operational levels. After the systematic review of the literature, the techniques of semi-structured interview, direct observation and document analysis were used. Content analysis was performed using the Atlas software. Ti 9.0. It was evident that the digitization of services and the use of innovative strategies that lead to ambidexterity are stimulated by the principles of Public Governance. Digitization provides greater accessibility to all hospital users and brought greater interactivity, reinforcing efficiency processes. In addition, it also contributes to the transparency of public acts, provision of services offered and responsiveness to citizens, contributing to the existence of good governance. The findings advance knowledge, by understanding the interaction between the digitalization-ambidexterity governance triad, and insofar as it broadens the managers' view of the influences of innovation strategies on digitalization practices.